The Non-Western World - Karan, Pradyumna P. (Taylor & Francis, 2004)
Through a cross-cultural and multi-disciplinary approach, this introductory textbook focuses on critical issues of development, environment, and cultural conflicts facing most area of the non-Western world. Areas covered include China, Japan, Southeast Asia, the Indian subcontinent, the Middle East, and sub-Saharan Africa.